Lutherrenaissance: past and present - Helmer, Christine; Holm, Bo Kristian (Forschungen zur Kirchen- und Dogmengeschichte, 2015)
"This volume approaches the current scholarly interest in Luther from the distinctive perspective of the Lutherrenaissance. Centered in Berlin at the turn of the twentieth century the Lutherrenaissance is significant for contemporary discussion because it shaped the reception of Luther and Lutheran theology for the rest of the century. Yet contemporary Luther scholarship, while inheriting the Lutherrenaissance's historical and conceptual categories, is also characterized by new approaches to Luther, specifically in recent years with a global orientation. While the subject of this volume is inspired by the original Lutherrenaissance, it surveys new ways in which Luther is studied in distinct and unprecedented contexts"--